Wireless Sensor Network Approach for Robust Localization of Mobile Nodes with Minimal Complexity - Fuentes, Michel Juan Carlos; Vossiek, Martin (Elektrotechnik und Informationstechnik, 2008)
Summary: The actual paper introduces a concept for localization of mobile nodes in a wireless sensor network. The realized algorithms are characterized by minimal complexity and high robustness even in networks with scarce resources. The implementation on simple, low-power embedded systems is possible without difficulty. An application of the concept for vehicle tracking illustrates the very good performance of the approach. © 2008 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2008.tech.IE.LEH.wirele
Keywords: Parameter estimation; Sequential Monte Carlo Method; Wireless localization